2021
DOI: 10.1021/acsami.1c08408
|View full text |Cite
|
Sign up to set email alerts
|

Highly Thermal Conductive Poly(vinyl alcohol) Composites with Oriented Hybrid Networks: Silver Nanowire Bridged Boron Nitride Nanoplatelets

Abstract: With the increasing demand for thermal management materials in the highly integrated electronics area, building efficient heat-transfer networks to obtain advanced thermally conductive composites is of great significance. In the present work, highly thermally conductive poly­(vinyl alcohol) (PVA)/boron nitride nanoplatelets@silver nanowires (BNNS@AgNW) composites were fabricated via the combination of the electrospinning and the spraying technique, followed by a hot-pressing method. BNNS are oriented along the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(49 citation statements)
references
References 56 publications
(76 reference statements)
1
48
0
Order By: Relevance
“…To solve the above difficulties, researchers found that introduction of other nanofillers into the BNNS‐filled polymer composites could further improve the TC while maintaining or improving the mechanical properties. Yang et al [ 29 ] introduced silver nanowire (AgNWs) into polyvinyl alcohol (vinyl alcohol) (PVA)/BN nanosheet composite and found that AgNWs with high‐aspect ratio can effectively construct heat grid by bridging with BNNS in the composite matrix. The in‐plane TC of PVA/BNNS@AgNW composites was 10.9 W·m −1 K −1 .…”
Section: Introductionmentioning
confidence: 99%
“…To solve the above difficulties, researchers found that introduction of other nanofillers into the BNNS‐filled polymer composites could further improve the TC while maintaining or improving the mechanical properties. Yang et al [ 29 ] introduced silver nanowire (AgNWs) into polyvinyl alcohol (vinyl alcohol) (PVA)/BN nanosheet composite and found that AgNWs with high‐aspect ratio can effectively construct heat grid by bridging with BNNS in the composite matrix. The in‐plane TC of PVA/BNNS@AgNW composites was 10.9 W·m −1 K −1 .…”
Section: Introductionmentioning
confidence: 99%
“…[34] Furthermore, the peak intensity of BN-OH markedly decreased, which could be attributed to the amorphous PS coated on the surface of BN. [45] The heat transfer performance of composites is usually closely related to their TC. To better highlight the advantages of the as-prepared BN-OH@mPS composite in heat transfer, BN/PS was prepared by the traditional melting approach for comparison.…”
Section: Resultsmentioning
confidence: 99%
“…Where λ is the thermal conductivity, α is the thermal diffusion, ρ is the density of the composite film, and Cp is the specific heat capacity (Yang et al, 2021a;Yang et al, 2021b). The results from Figure 5, show that controlling both the amount of BNNS filling and the concentration of the suspension results in enhanced thermal diffusion and thermal conductivity of the CNF/BNNS composite film in the in-plane direction (Zhou et al, 2016;Wu et al, 2017;Wu et al, 2018;Yan et al, 2021b).…”
Section: Thermal Transportation Properties Of Cnf/ Bnns Composite Filmsmentioning
confidence: 99%
“…We have investigated the in-plane thermal conductivity of the CNF/BNNS composite films in these two ways, particularly the effect of varying the suspension concentration with a 90% BNNS filler content. The composite films show good thermal conductivity and can be used as a heat spreader for electronic devices (Yang et al, 2021a;Zhang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%